Awareness of impacts of salinity intrusion on livelihoods: Evidence from southern coastal rural areas of Bangladesh - Masudul Alam; Mokbul Morshed Ahmad; Takuji W. Tsusaka; Malay Pramanik (Current Research in Environmental Sustainability)
Abstract:: Salinity intrusion is a widespread issue across coastal areas. There remains a lack of evidence regarding awareness of the impacts of salinity intrusion on livelihoods in coastal areas, particularly in terms of how this awareness affects preparedness and the development of strategies. The paper aims to assess the awareness of the impacts of salinity intrusion among southern coastal inhabitants in Bangladesh from a comparative perspective. A survey was conducted with 400 households in Kalapara, Taltali, and Patharghata sub-districts of Bangladesh, which was analyzed with descriptive and inferential statistics. The chi-squared test shows that salinity intrusion is associated with factors such as saline water flow (p < 0.10). In addition, 46 % of the respondents from the high-salinity sub-districts perceive prevalence of numerous diseases such as diarrhea, cholera, and skin infections (p < 0.01) significantly higher compared to moderate-salinity areas. Very high levels of awareness (WAI = 0.78, 0.76) of groundwater salinity are observed in the high-salinity sub-districts (p < 0.01). Moderate awareness of the impacts on winter season rice was found across the three areas (p < 0.01), while Kalapara showed higher awareness (WAI = 0.53, 0.65) of the impacts on cereals and health, respectively. Awareness of other impacts, such as on land use, aquaculture, mangrove, and coastal resources, was found to be lower. Significant regional differences in awareness exist across the three regions. The findings suggest improving education and access to information to increase awareness, and help communities adopt area-specific adaptation measures to alleviate adverse effects on health, agriculture, and environments.